Gender and Racial Differences in Peer Effects of Limited English Students: A Story of Language or Ethnicity? - Timothy M. Diette; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2016)
There is a perception among native born parents in the U.S. that the increasing number of immigrant students in schools creates negative peer effects on their children. In North Carolina there has been a significant increase in immigrants especially those with limited English language skills and recent data suggest that North Carolina has the 8th largest ELL student population with over 60 percent of immigrants coming from Latin America and the Caribbean. While past research suggests negative though negligible peer effects of Limited English (LE) students on achievement of other students, potential peer effects of student from Latin America in general has not been considered. In this paper we attempt to identify both LE student and Latin American (LA) student peer effects separately utilizing fixed effects methods that allow us to deal with the potential selectivity across time and schools. On average we find no evidence of negative peer effects of LE students on females and white students but note small negative effects on average on males and black students. We also find that, holding constant other factors, an increase in the share of LA students share does not create negative peer effects on native students' achievement. Rather, it is the limited English language skills of some of these students that leads to small, negative peer effects on natives.
Keywords: I20; I21; J15; J24; 330; immigrants; student achievement; peer effects; education; race; gender; Limited English students; Latino peer effects; Hispanic peer effects